National statistical news: Oct. 1979 - Sept. 1980 - Government statisticians of Nigeria (Akure ministry of economic planning and statistics, 1980)
This book is an embodiment of the activities of all Government statisticians. It collate and examine the work force in various states across Nigeria to ascertain the gender inequities, educational status and deficit in standard of living for a teeming population.
asm; 06/03/19
Loans
Keywords: Prices-consumer price index; Nigeria